Os corpos da via crucis: o efeito cômico em Clarice Lispector - Ferreira, Eliliane Santos (2021)
The aim of this research is to approach the female body and the comic effect in the work A via crucis do corpo (1974), a compilation of short stories by Clarice Lispector that carries a different theme from her other works, and that therefore did not have the same critical acceptance . Composed of thirteen short stories, it tells us about topics such as sexuality at the best age, masturbation and betrayal. The classifications he received covered up his true and real potential, however, the scenario facing this work has been changed from the critical feminist perspectives and gender studies. We will approach two biases present in this lispectorian text, which will be the body of the female characters and the comic effect. For the construction and argumentation of the first point, we used authors such as David Le Breton (2010) and Elódia Xavier (2007), while for the construction of the comic we started from the conceptions of Henri Bergson (2007) and Sigmund Freud (1905), warning that so many others of such importance are still added in the course of the research, such as Benjamin Moser (2009), Vilma Arêas (2005), Gérard Genette (2009) and others. This research is based on a qualitative method, based on theoretical records for the reading and analysis of the thirteen short stories. The aim is to show that the body / comic relationship takes place in the course of all narratives, seeking to emphasize the studies of this relationship and the work in question, since we note that there are no previous reflections that deepen such aspects in that work.